1993
DOI: 10.1111/j.1600-0668.1993.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 of the California Healthy Building Study: A Summary

Abstract: Twelve public office buildings were selected for a study of relationships between worker's health symptoms and a number of building, workspace, job, and personal factors. Three buildings were naturally ventilated, three were mechanically ventilated, and six were air conditioned. Information on the prevalences of work‐related symptoms, demographics, and job and personal factors were determined via a questionnaire completed by 880 occupants. Several indoor environmental parameters were measured. Logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 14 publications
(29 reference statements)
4
46
3
Order By: Relevance
“…Reactive oxygenated VOC, like formaldehyde and acrolein and other species, are, among other things, formed from these atmospheric reactions, which can occur within the timeframe of low air exchange rates (182). In addition, this hypothesis about reactive species is supported by the fact that ozone-emitting equipment (eg, photocopiers) that can contribute to these reactions locally have been associated with eye and airway irritation (105); it is also supported by the results of a recent eye exposure study of eight men (183).…”
Section: Gaseous Pollutantsmentioning
confidence: 74%
See 1 more Smart Citation
“…Reactive oxygenated VOC, like formaldehyde and acrolein and other species, are, among other things, formed from these atmospheric reactions, which can occur within the timeframe of low air exchange rates (182). In addition, this hypothesis about reactive species is supported by the fact that ozone-emitting equipment (eg, photocopiers) that can contribute to these reactions locally have been associated with eye and airway irritation (105); it is also supported by the results of a recent eye exposure study of eight men (183).…”
Section: Gaseous Pollutantsmentioning
confidence: 74%
“…Use of office equipment, especially work with a VDU, handling photocopy paper, and work near a photocopier are often associated with irritation of the eyes and upper airways (4,7,105 Different building-related, person-related, and psychological factors are also associated with eye irritation. Some cross-sectional epidemiologic studies have shown an association between VDU work and eye irritation, and, despite major differences in materials and methods, a dose-response effect of VDU workhours appears to be associated with eye irritation (4,18,108).…”
Section: Epidemiology Of Eye Symptoms In Office Environmentsmentioning
confidence: 99%
“…Buildings within which occupants experience unusually high levels of these symptoms are sometimes called sick buildings. Some non-specific health symptoms are experienced frequently by a substantial fraction of all office workers (e.g., Brightman et al 1997, Fisk et al 1993;…”
Section: Non-specific Health Symptomsmentioning
confidence: 99%
“…Improved or degraded lighting quality are possible depending on placement and optical characteristics of building elements that provide daylight. There is some evidence that proximity to windows, even when they can not be opened, is associated with a decreased frequency of acute non-specific building-related health symptoms (Fisk et al 1993). …”
Section: Linkages Between Energy Conservation Measures and Ieqmentioning
confidence: 99%
“…[1][2][3][4][5] There is evidence that temperature and relative humidity may be partially responsible,6 but apart from descriptions of outbreak situations, there is very little populationbased evidence for the role of chemical or biological contaminants.6 '7 Failure to detect exposure-response relationships between work-related symptoms and chemical or biological contaminants may result from misclassification of exposure, because of spatial810 or temporal variability,1-'3 particularly if exposure for all workers in a building is based on measurement of environmental factors made at a few sites,3'1416 at a different time than measurement of symptoms,16 or over a short period of time.3'15 '16 In addition, symptoms may result from the combined effect of exposure to multiple contaminants, each at low concentrations.17 '18 We have completed a randomized double-blind study of experimental manipulation of outdoor air supply in office buildings. In this study, workers completed questionnaires each week while environmental parameters were measured; this allowed a within-subject estimate of the association of symptoms and concentrations of individual or multiple contaminants.…”
Section: Introductionmentioning
confidence: 99%